(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Food poisoning is a common health problem caused by consuming contaminated food. This study aimed to investigate the characteristics of food poisoning in the Kenitra region between 2012 and 2022, including age, gender, contamination sources, treatment outcomes, types of food involved, and preparation methods. Methods Data on food poisoning cases were collected, and statistical analysis, including multiple correspondence analysis (MCA), was performed to identify factors contributing to food poisoning. Cronbach’s alpha was calculated to assess the internal consistency of the MCA variables. Results Children aged 5 to 15 accounted for nearly half of the reported food poisoning cases (48.9%), with a higher prevalence among females (59%) compared to males (40%). Food poisoning incidents were more prevalent in rural areas (63.4%) than in urban areas (36.6%). Canned products were responsible for 40% of the cases. Main dishes of animal origin, including snails, turkey, fish, chicken, and minced meat, were the most commonly involved food category (88.9%). The majority of patients sought medical attention within 5 hours of contamination (77.1%), and most experienced positive outcomes (92.7%). Conclusion This study provides valuable insights into the factors contributing to food poisoning in the Kenitra region. Multiple correspondence analysis revealed that the type of food, place of contamination, and preparation method significantly influenced the contamination rate and treatment outcomes. These findings emphasize the importance of preventive measures and appropriate management strategies to mitigate food poisoning cases. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 97-102